Juridical Analysis of Patient Safety Policies in Hospitals in Indonesia - Asep Nurman Hidayat; Made Santika; Odang Suparman (Jurnal Ilmiah Dunia Hukum, 2025)
Patient safety is a core element of the healthcare system, aimed at preventing adverse events and improving service quality. In Indonesia, it is governed by Law Number 17 of 2023 on Health and Minister of Health Regulation Number 11 of 2017 on Patient Safety, yet implementation remains uneven. Many hospitals show low compliance, government monitoring is limited, and significant gaps persist between urban and rural facilities. This study examines the legal framework and effectiveness of patient safety policies using a normative juridical method with statutory and conceptual approaches. Primary legal sources, including laws and regulations, along with secondary academic references, were analyzed qualitatively through a deductive process. The results indicate that although the regulatory framework provides comprehensive guidance, its execution in practice is still inadequate. Persistent obstacles include insufficient transparency in incident reporting, weak legal oversight, limited training for healthcare workers, and restricted access for patients to essential medical information. The study concludes that improving patient safety requires stronger hospital accountability, more transparent reporting mechanisms, and enhanced protection of patient rights within the legal system. Strengthening these aspects is expected to support safer and higher-quality healthcare services while providing greater legal certainty for patients in Indonesia.